Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf02242998
|View full text |Cite
|
Sign up to set email alerts
|

D-penicillamine induced myasthenia gravis in rheumatoid arthritis: An unpredictable common occurrence?

Abstract: Five patients out of 71 with rheumatoid arthritis (RA), who received D-penicillamine, developed myasthenia gravis (MG) within a two-year period. They all responded promptly to discontinuation of the drug and pyridostigmine administration. None of the patients had anti-Ro(SSA) antibodies or features of Sjögren's syndrome, whereas three of the five had the HLA-DR1 phenotype. The relatively high frequency of MG observed in our population, along with its unpredictability and potentially serious sequelae, necessita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…These are predominately autoimmune peripheral nerve disorders such as chronic inflammatory demyelinating polyneuropathy, Guillain‐Barré syndrome, and mononeuritis 4, 17, 36, 40. Drug‐induced MG is a well‐described occurrence in patients with RA treated with penicillamine, but it has not been reported previously with etanercept therapy 1, 9, 11, 28. Although etanercept has been shown to be beneficial in MG, 3 of the 11 patients studied by Rowin et al37 did not complete the study because of worsened symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These are predominately autoimmune peripheral nerve disorders such as chronic inflammatory demyelinating polyneuropathy, Guillain‐Barré syndrome, and mononeuritis 4, 17, 36, 40. Drug‐induced MG is a well‐described occurrence in patients with RA treated with penicillamine, but it has not been reported previously with etanercept therapy 1, 9, 11, 28. Although etanercept has been shown to be beneficial in MG, 3 of the 11 patients studied by Rowin et al37 did not complete the study because of worsened symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, D-penicillamine (used in the treatment of rheumatoid arthritis) was known to induce AChR Ab-positive MG in up to 7% of treated patients. 34,35 In contemporary practice, MG is now increasingly being recognized as a complication of immune checkpoint inhibitors (ICPis). These medications are being increasingly used to upregulate the immune system to target a variety of malignancies.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…When studying the effects of different calcium channel blockers on transmitter release at the neuromuscular junction, it was found that P-type calcium channel blockers inhibited nerve-evoked action potentials and subsequent synaptic transmission, while transmitter release remained unaffected by selective L-type and N-type channel blocking agents (Protti et al, 1996). These findings underscore that P-type channels Vincent et al, 1978;Aldrich et al, 1979;Albers et al, 1981;Kuncl et al, 1986;Drosos et al, 1993;Andonopoulos et al, 1994;Adelman et al, 1995;Penn et al, 1998 Chloroquine Anti-malarial drug that prevents biocrystallization of heme Parmar et al, 2002;Cartwright et al, 2004;Purvin et al, 2006;Oh et al, 2008;Khalid et al, 2016 Ach, Acetylcholine; AChR, Acetylcholine receptor; COVID-19, coronavirus disease 2019; CTLA4, cytotoxic T-lymphocyte-associated protein 4; EMG, Electromyography; GVHD, Graft-versus-host disease; HSCT, Hematopoietic stem cell transplantation; HMG-CoA reductase, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase; IFN, Interferon; MG, Myasthenia gravis; PD-1, Programmed cell death protein 1; PD-L1, Programmed cell death 1 ligand 1; Th2, T helper type 2.…”
Section: Calcium-dependent Presynaptic Effectsmentioning
confidence: 93%